Insect management with refugia plant in upland rice (Oryza sativa L.). (May 2019) - Sutriono,; Purba, E; Marheni,
Abstract: Refugia is a microhabitat that provides spatial or temporal shelter for pest natural enemies, and supports biotic interaction components in ecosystems, such as pollinators or pollinating insects. The research objective was to study the best types of refugia plant in pest insect management. The treatments consisted of five plant refugia, R0 (control), R1 ( Ageratum conyzoides ), R2 ( Axonopus compressus ), R3 ( Cosmos caudatus ), and R4 ( Wedelia trilobata ) and each treatment was made in five replicates. This research is descriptive using the transect method and sampling is done using several tools, namely: yellow traps, pitfall traps and sweep nets . The findings indicate that the highest pest insect in refugia's composition is R0 as many as seven species, and R2 does not have the highest composition of insect pests due to predator domination over insect pests. The highest predator insects found in R2 is four species, while R1 didn't have the highest composition of predator insects. Data on morphospecies diversity index of pest and predator insect are moderate. Evenness index of morphospeciesis fall in high criteria, ≥ 0.6.